50 Years in Space Science - Charles F. Kennel (Perspectives of Earth and Space Scientists)
Abstract These are my personal recollections of my 50‐year involvement in planning NASA space projects, including the Voyager Missions, The Hubble Space Telescope, the International Space Station, the Space Shuttle, the Falcon Space X launcher, and the James Webb Space Telescope.